Have superheavy elements been produced in nature? - Petermann, I.; Langanke, K.; Martínez-Pinedo, G.; Panov, I. V.; Reinhard, Paul-Gerhard; Thielemann, F. K. (European Physical Journal A, 2012)
We discuss the possibility whether superheavy elements can be produced in Nature by the astrophysical rapid neutron capture process. To this end we have performed fully dynamical network r-process calculations assuming an environment with neutron-to-seed ratio large enough to produce superheavy nuclei. Our calculations include two sets of nuclear masses and fission barriers and include all possible fission channels and the associated fission yield distributions. Our calculations produce superheavy nuclei with A ≈ 300 that however decay on time scales of days. © Società Italiana di Fisica / Springer-Verlag 2012.
CRIS-Team Scopus Importer:2023-07-24